2016
DOI: 10.3233/jad-160111
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted White Matter Network and Cognitive Decline in Type 2 Diabetes Patients

Abstract: Abstract. Type 2 diabetes mellitus is accompanied by cognitive impairment and is associated with an increased risk of dementia. Damage to brain structures such as white matter network disruption may underlie this cognitive disturbance. In the present study, 886 non-diabetic and 163 type 2 diabetic participants completed a battery of neuropsychological tests. Among them, 38 diabetic patients and 34 non-diabetic participants that matched the patients for age/sex/education received a magnetic resonance imaging-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
36
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 39 publications
7
36
1
Order By: Relevance
“…It has been shown that diabetes mellitus is accompanied by cognitive declines and associated with an increased risk of dementia [15]. In the present study, MWM results showed that there are significant differences between normal and diabetic rats, indicating that diabetes is related to cognitive impairment.…”
Section: Discussionsupporting
confidence: 53%
“…It has been shown that diabetes mellitus is accompanied by cognitive declines and associated with an increased risk of dementia [15]. In the present study, MWM results showed that there are significant differences between normal and diabetic rats, indicating that diabetes is related to cognitive impairment.…”
Section: Discussionsupporting
confidence: 53%
“…Recently, T2DM‐related structural disconnection has been further supported by WM topological network analyses using graph theory. Three studies on structural network analysis in T2DM patients have detected a weaker small‐world property and decreased local or global efficiency in T2DM patients . However, these studies focused either on elderly patients or on patients with diabetes complications and severe cognitive impairment .…”
Section: Introductionmentioning
confidence: 99%
“…Three studies on structural network analysis in T2DM patients have detected a weaker small‐world property and decreased local or global efficiency in T2DM patients . However, these studies focused either on elderly patients or on patients with diabetes complications and severe cognitive impairment . However, chronic hyperglycemia could lead to end‐organ damage, whereas cognitive impairments have been found to occur in the early stages of T2DM .…”
Section: Introductionmentioning
confidence: 99%
“…Altered network and structural connectivity in type 2 diabetes have been shown using tractography (Reijmer et al, 2013a,b; Hoogenboom et al, 2014; van Bussel et al, 2016b; Yang et al, 2016; Zhang J. et al, 2016). Local and global network properties (i.e., cluster coefficient, global efficiency, path length) were altered and associated with impaired processing speed (Reijmer et al, 2013b).…”
Section: White Matter Tract Abnormalitiesmentioning
confidence: 99%
“…Microstructural abnormalities have been published for various brain regions in type 2 diabetes (Yau et al, 2009, 2010; Falvey et al, 2013; Zhang J. et al, 2014, 2016; van Bussel et al, 2016b; Xiong et al, 2016). Reduced FA has been observed in the white matter (Yau et al, 2010; Falvey et al, 2013) mostly concentrated in frontal and temporal regions (Yau et al, 2009), while elevated ADC values were found in a number of brain regions, including the hippocampus (Falvey et al, 2013) and multiple gray matter regions (Yau et al, 2010).…”
Section: White Matter Tract Abnormalitiesmentioning
confidence: 99%